PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI STRATEGI PROMOSI PRODUK LOKAL: STUDI KASUS KAOS NYENYES PALEMBANG - Fiansi Dwi Arista (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This study discusses the utilization of the social media platform Instagram as a promotional strategy for local products by Kaos Nyenyes Palembang. Using a qualitative descriptive method, this research shows that features such as feed, stories, reels, and highlights are used to display creative content based on local culture through humor, local language, and Palembang's distinctive design. This strategy not only increases consumer appeal and loyalty but also strengthens cultural identity and fosters pride in local products. The research results confirm that digital promotion based on local wisdom is effective in expanding market reach and building the image of SMEs that are modern and culturally valuable